The Influence of Artificial Intelligence on Readiness and Acceptance of Technology in E-Commerce - Naskiroh, Naskiroh; Nurqolbiyah, Dina; Winarti, Winarti; Rosnidah, Ida; Hidayat, Firman (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
The use of artificial intelligence in e-commerce makes it easier for users to do online shopping. However, user data collection carried out by artificial intelligence in e-commerce can be misused. This is a shift in intention to adopt artificial intelligence in e-commerce. This study aims to identify the factors that impact the adoption of artificial intelligence in the field of e-commerce. The technology readiness model and the technology acceptance model are both utilized in this study. Data was collected from 283 students who have done shopping in e-commerce. The data collected will then be analyzed using SEM-PLS. The findings suggest that optimism, innovativeness, and discomfort have a role in shaping the acceptability of artificial intelligence in e-commerce, through the perceived ease of use and perceived usefulness. However, research findings suggest that there is no correlation between insecurity and the perceived ease of use and usefulness. The findings suggest that the way users view the ease of use, and the utility of artificial intelligence technology directly influences their acceptance of it in e-commerce, which is then through in their intention to use it. The result of this study can be used by online businesses to apply TAM and technology readiness models to maximize the use of AI in e-commerce.